Aktivitas Air Rebusan Daun dari Beberapa Tumbuhan dalam Menekan Pertumbuhan Sclerotium rolfsii Sacc. Penyebab Busuk Batang pada Tanaman Kacang Tanah secara In Vitro: english - Martinius, Martinius; Gani, Suardi; Ningsih, Juita Wilna (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2019)
The leaves of some plants have been proved to suppress the development of plant diseases caused by pathogens. The study aimed to determine the water decoction of leaves to suppress the growth of S. rolfsii caused stem rot on peanuts in vitro. The study was conducted in the Laboratory of Phytopathology Departement of Plant Pest and Disease Faculty of Agriculture, Andalas University, from May-July 2015. The experimental design was a Randomized Complete Design (RCD) with seven treatments and six replications. The treatments were control, water decoction of Annona squamosa, Impatiens balsamina, Eclipta alba, Cymbopogon citratus and Tithonia diversifolia with concentration of 0,5% and fungicide with tebukonazol active ingredient at a concentration of 0,1%. Variables observed were macroscopic fungal culture, colony area, wet and dry weight of colonies. Data were analyzed by using ANOVA and DNMRT at a 5% of significance level.. The results showed that all water decoctions of plant leaves were able to suppress the growth of S. rolfsii. The most active of the water decoction was from T. diversifolia with suppression to colony area reached 77,32%, and wet and dry weight were 77,24% and 84,66%, respectively.